MAIN DETERMINING FACTORS OF INTEREST AND MOTIVATION IN LEARNING AMONG ELEMENTARY SCHOOL STUDENTS - Situmorang, Rica Elisabeth; Hanifah, Rifdah; Aprilia, Rika; Budiarti, Risma Hasna; Yanti, Riska Risma; Iskandar, Sofyan (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2026)
This study aims to identify and analyze the main determinant factors that most dominantly influence the interest and learning motivation of Elementary School (SD) students. Fluctuations in interest and motivation are often the main obstacles to achieving optimal learning outcomes at the elementary level. The research employs a Systematic Literature Review (SLR) method, involving the critical identification, evaluation, and synthesis of relevant primary studies. The synthesis of empirical findings indicates that students' interest and motivation are significantly influenced by both internal and external factors. Internal factors include students' physical and mental condition, intelligence, and attitude towards the lesson, while the most dominant external factors relate to the teacher's role, encompassing teacher creativity in varied methods and media usage, and creating a conducive classroom environment. Furthermore, environmental support, particularly the role of parents and the availability of facilities, is also a crucial determinant. Intrinsic motivation factors, such as drive, needs in learning, and future aspirations, were found to be quite dominant. These findings confirm that effective learning strategies must be student-centered and supported by improving teacher competency in classroom management and instructional innovation, as well as active collaboration with parents.